Mexico Public Expenditure Review - World Bank (Washington, DC, 2016)
This Public Expenditure Review (PER) was prepared at the request of Mexico’s Ministry of Finance and Public Credit (Secretaría de Hacienda y Crédito Público, SHCP); its analysis of the efficiency, equity and impact of public spending in selected sectors is designed to inform Mexico’s ongoing process of fiscal consolidation. The Mexican government’s hard-earned reputation for fiscal responsibility and sound macroeconomic management has provided a solid foundation for stability and growth. As Mexico strives to meet the challenges of a dynamic global economic environment, this PER is intended to support the government’s efforts to adjust expenditure policies to better reflect the country’s evolving macro-fiscal circumstances. The PER is organized into two sections; the first focuses on overarching public expenditure management and cross-cutting policy issues. Chapters two through five examine the national macro-fiscal profile, selected issues in fiscal decentralization, the budget process, the performance evaluation system and human resource management in the public administration. These chapters explore how a combination of revenue shocks and structural expenditure pressures is affecting Mexico’s public finances and consider the implications of these trends over the medium term. They evaluate the extent to which federal budgetary inertia reflects sector-level policy commitments and describe how built-in expenditure rigidities can complicate the medium-term consolidation process. Chapters’ six through twelve each focus on a sector with especially significant fiscal implications: health; education; social assistance and labor market programs; subsidies for rural development, housing and small-businesses support; water and sanitation infrastructure; and public security. These sector-level analyses explore the combination of demographic trends and policy commitments that are driving a secular increase in both expenditure pressures and budgetary rigidities. The government’s policy goal of achieving universal secondary education will permanently increase the education budget, while universal access to basic health insurance will drive a similar structural expansion in public spending on health, which will be compounded by the rising healthcare costs of an aging population. These same demographic trends will also intensify pressure on the social protection budget. The rapid expansion of the police and security services will entail significant long-term spending commitments, and the fiscal impact of accelerated hiring will be magnified by the incorporation of nearly half a million municipal police into the national police force. Taken together, these trends will greatly increase aggregate public spending in Mexico over both the medium and long term.